KONDISI KRITIK SASTRA INDONESIA SEABAD H.B. JASSIN (Indonesia Literary Criticism in A Century of H. B. Jassin) - Puji Santosa (Kantor Bahasa Sulawesi Tenggara, 2017)
This study aims to reveal and to describe the condition of Indonesian literary criticismin a century of H.B. Jassin (1917-2017). The research problem is how the condition of Indonesian literary criticism in a century of H.B. Jassin? The method used is the historical and descriptive method. The research proves that the condition of Indonesian literary criticism in a century of H.B. Jassin progressing quite encouraging on four genres of literary criticism, namely: (1)general literary criticism or practical literary criticism developed in printed media and electronic, (2) history of academic literary that thrives in academic research focusing on philology, (3) literature appreciation and interpretation that developes in the academic and scientific journal of literature, and (4) literary theory that developes in academic world as a basic reference for writing literature scientific papers. From these results it can be concluded that the condition of Indonesian literary criticism in a century of H.B. Jassin has never been stagnant or vacuum.